Optical properties enhancement with multilayer coating technique of additive-enhanced zinc oxide nanostructure for fiber Bragg grating humidity sensor - Riza, Muhammad Arif; Yun, Ii Go; Maier, Robert R. J.; Harun, Sulaiman Wadi; Ahmad Anas, Siti Barirah (John Wiley & Sons, 2021)
A humidity sensing material is usually hygroscopic in nature and can allow sites for water adsorption. The hygroscopic material is usually coated in various devices for sensing enhancement. A zinc oxide additive-enhanced nanostructure (ZnO-HMT) was coated repeatedly on fiber Bragg grating (FBG) have been fabricated. The sensing material was synthesized for the purpose of characterizing its capability in enhancement of relative humidity sensing of uniformly grated core optical fibers with multiple layers of sensing layer. The coating and annealing process was repeated for at least three times resulting three layers of ZnO-HMT coated on an FBG fiber. Observed microscopy images showed that the thickest coating began to form larger lumps on the sensor surface, but absence of any gaps present. Reflectivity power was observed to be greatest for triple layered samples due to the coating possibly containing the light propagation and prevent evanescent leakages. Analysis with optical spectrum analyzer detects notable wavelength shifts at sensing range of 60–80 %RH and a significant increase of sensitivity for triple layered samples.